An Aggregate View of Macroeconomic Shocks in Sub-Saharan Africa: A Comparative Study Using Innovation Accounting - Simeon Coleman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This paper investigates the impacts and responses of macroeconomic shocks in some domestic economies in Sub-Saharan Africa over the period 1961-99; more specifically, it seeks to answer the question of whether there are any systematic differences in the responses of the CFA franc zones and the non-CFA franc zone countries to macroeconomic shocks. Based on the Blanchard-Quah methodology, we identify shocks to the changes in real exchange rate and output using a structural VAR (SVAR) model for these small open economies. Our finding that the real exchange rate innovations in the CFA franc zones are largely independent of domestic variables suggests that external influence is more important in the CFA zones. There is also some evidence that money demand shocks are more significant in the non-CFA franc zone countries. Finally the analyses suggest that shocks tend to persist in the non-CFA countries and less so in the CFA franc zone. A comparison of both the short-run and long-run responses of each franc zone and the non-CFA countries suggests that being in the monetary union ensures that the CFA franc zone respond differently to macroeconomic shocks, and have more stable macroeconomies.
Keywords: 330; structural VAR models; innovations; Sub-Saharan Africa